Airborne fungal spore relationships with meteorological parameters and skin prick test results in Elazig, Turkey - Kilic, Mehmet; Altunoglu, Mustafa Kemal; Akdogan, Gul Esma; Akpinar, Salih; Taskin, Erdal; Erkal, Ahmet Hamdi (Springer, 2020)
Background Since fungi spores have high concentrations in the atmosphere during most of the year, they have an important place in respiratory allergies. In this regard, the preparation of calendars showing fungi spore loads for residential areas has much importance in the treatment of the patients. The first aim of this study was to present the airborne fungal spore research results from Eastern Anatolia in Turkey. Then, the mold spores' relationships with the meteorological parameters and skin prick test results were also evaluated. The presence of fungal spores was investigated using a volumetric spore trap in 2018 year. Methods In this study, fungal spores within the atmosphere of the Elazig city of Turkey was measured through the volumetric method, using a Lanzoni VPPS 2000 device (VPPS 2000 Lanzoni, Bologna, Italy), in 2018 year. Annual data of temperature, humidity, precipitation and wind speed were used for comparing meteorological data with airborne fungal spore counts. In addition, 637 children who were admitted to a pediatric allergy clinic with allergic complaints were enrolled in the study. Results A total of 145,099 spores/m(3)and 20 fungal taxa belonging to the molds were recorded.Ustilagowas the predominant genus (18.10%), followed byOidium(18.01%),Drechslera(12.82%), andFusarium(11.60%), which were the most common fungal spores found in Elazig's atmosphere. The total mold spores in the atmosphere reached the highest level, with 28,153 spores/m(3), in July (mid-summer). Moreover, we found a positive correlation between the mold spores and the temperature, but negative correlations with the humidity and wind speed. In the skin prick tests in the children with allergic complaints, we detected sensitization toAlternaria alternatain 4.4%,Cladosporium herbarumin 3.0%,Penicillium notatumin 1.4%, andAspergillus fumigatusin 1.1%. Additionally, there was no correlation between fungal spore concentration in the atmosphere with fungal spores sensitization in the skin prick test. Conclusions This study was the first aerofungal survey of the Eastern Anatolia region in Turkey; therefore, new information has been introduced in the field of aerobiology in Turkey.
Keywords: Airborne fungal spores; Meteorological parameters; Skin prick test; Volumetric method; Turkey